The Effectiveness of Total Physical Response (TPR) in Developing Students’ Maharat al-Kalām at MTs Negeri 2 Banggai - Wiranto Talibo; Moh. Sabiq Rabbani (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2026)
This study examines the effectiveness of Total Physical Response (TPR) in developing students’ Arabic speaking ability (maharat al-kalām) at MTs Negeri 2 Banggai. A quasi-experimental design with a non-equivalent control group was applied to 32 seventh-grade students divided into an experimental class taught through TPR and a control class taught through conventional lecturing. Data were collected through oral pre-test and post-test, classroom observation, student questionnaires, and a teacher interview, and were analyzed using normality and homogeneity tests, Independent Samples t-test, and N-Gain. The experimental group showed a much larger gain in speaking scores than the control group, with N-Gain in the moderate category compared with low effectiveness for the control class, and the difference between groups was statistically significant. The findings indicate that TPR has a meaningful positive impact on students’ Arabic speaking skills and offers a promising pedagogical alternative for madrasah contexts.